PENANAMAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI KEGIATAN KEISLAMAN DI MI ALMAARIF 02 SINGOSARI - Mia Aisyah Rahma; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
What is the Investigation? How to cultivate religious character? The cultivation of religious character is the stage of inculcating moral or religious values so that they become habits. The problem that often arises in the world of education today is the problem of the character of the students that can be seen in their behavior. Lately, there are many students who commit violence against their friends, both physically and mentally, the way they talk and behave with someone who is still missing can be the cause of the decline in character education. One way to overcome these problems is to instill character education values in students. Faced with this reality, MI Almaarif 02 Singosari carried out various Islamic activities to inculcate the religious character of the students. This research was carried out using descriptive qualitative research. Data were collected by observation, interviews and documentation. Then, data analysis techniques carried out include data condensation, data presentation and drawing conclusions.